Factors that affect the consumption of electricity in refrigerators in the Forastero sector, Latacunga Canton, Belisario Quevedo Parish during the period of January-February 2024 - Flores, Bryan Omar (Multidisciplinar (Montevideo), 2025)
Introduction: the increase in electricity demand on a global scale implies damage to the Earth's biodiversity. Several Latin American countries experienced a significant economic increase, which generated a greater demand for energy.Objective: to determine the factors that affect electricity consumption in the foreign sector, Latacunga canton, Belisario Quevedo parish, during the period from January to February 2024.Method: an observational, descriptive and cross-sectional study was carried out on the factors that affect electricity consumption in the foreign sector, Latacunga canton, Belisario Quevedo parish, during the period from January to February 2024.Results: 87 % of the total sample have only one refrigerator, 50 % open the door more than five times a day, respondents do not spend time performing the corresponding maintenance for their refrigerator, 100 % do not know the energy efficiency rating of their refrigerators, and indicated that the use of technologies such as programming and energy and temperature savings has a high impact on electricity consumption, which is 75 %.Conclusions: the critical importance of energy efficiency in the use of refrigerators is highlighted, and the need to raise awareness among users about practices they can adopt to significantly reduce electricity consumption is underlined